Innovative Learning Models in The Merdeka Curriculum - Nurhaswinda Nurhaswinda; Heri Kurniawan; Ulfa Rahmadhani; Rahmiatul Fitri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This article discusses innovative learning models within the framework of the Merdeka Curriculum, including Problem Based Learning (PBL), Project Based Learning (PjBL), Discovery Learning, and Differentiated Learning. The research aims to explore the application of each model in enhancing student engagement, motivation, and learning outcomes. The PBL model emphasizes real-world problem-solving, encouraging students to think critically and creatively. PjBL offers students opportunities to engage in relevant projects, fostering collaborative and managerial skills. Discovery Learning focuses on exploration and discovery, allowing students to understand concepts through hands-on experiences. Meanwhile, Differentiated Learning adapts teaching methods to meet the diverse needs and abilities of students, creating an inclusive learning environment. Analysis results indicate that the implementation of these models significantly enhances 21st-century skills, including critical thinking, creativity, and collaboration. Furthermore, these models have been shown to reduce student boredom and increase active participation in the learning process. These findings underscore the importance of integrating innovative learning models within the Merdeka Curriculum to support more effective and enjoyable learning experiences. This article is intended to serve as a reference for educators in effectively implementing these models in the classroom, as well as providing insights for curriculum developers in designing learning strategies that are more responsive to the needs of students in the modern era.